Unsuccessful pedagogical situations - Victoria V. Dobrova (Вестник Самарского государственного технического университета. Серия: Психолого-педагогические науки)
On the basis of the previous theoretical and practical research conducted by the author, in this paper the concept of pedagogical situation is studied. The suggested classification of pedagogical situations is based on the ability of a pedagogical situation to solve pedagogical tasks, reach pedagogical problems, achieve a pedagogical effect and thus to become a pedagogical event. On these basis as well as on the logic and practice of a teacher's everyday work, the three types of situations were previously identified. One type of these situations is described in this paper. The goal of such situations is unachievable, which means that the situation can not change from a potential situation to an actual situation. The goal-oriented principle of analysis opens up the prospect of establishing relationships between all the parameters of the situation and the personal characteristics of its participants. The scheme for describing pedagogical situations logically includes the following components: participants (teachers and students a potential pedagogical agent), goal/task, conditions (locus).